New Insights into 5hmC DNA Modification: Generation, Distribution and Function - Shi, Dong-Qiao; Ali, Iftikhar; Tang, Jun; Yang, Wei-Cai (Frontiers in Genetics, 2017)
Abstract Dynamic DNA modifications, such as methylation/demethylation on cytosine, are major epigenetic mechanisms to modulate gene expression in both eukaryotes and prokaryotes. In addition to the common methylation on the 5th position of the pyrimidine ring of cytosine (5mC), other types of modifications at the same position, such as 5-hydroxymethyl (5hmC), 5-formyldeoxy (5fC), and 5-carboxy (5caC), are also important. Recently, 5hmC, a product of 5mC demethylation by the Ten-Eleven Translocation (TET) family proteins, was shown to regulate many cellular and developmental processes, including the pluripotency of embryonic stem cells, neuron development, and tumorigenesis in mammals. Here, we review recent advances on the generation, distribution and function of 5hmC modification in mammals and discuss its potential roles in plants.